Pengembangan Kemampuan Berpikir Kritis Siswa melalui Pelatihan Kimia Komputasi Menggunakan Avogadro dan ChemDraw di SMAN 3 Banjar - Thoriq, Thoriq; Sri Rahayu, Rizky; Firdaus Ramdhani, Zidhan; Sarirah, Thayyibah (MASALIQ, 2025)
Critical thinking skills are essential competencies that students must possess to face the challenges of the Industry 5.0 era. One innovative method to develop these skills is through computational chemistry training using Avogadro and ChemDraw software. This study aims to evaluate the effectiveness of computational chemistry training in enhancing students' critical thinking skills at SMAN 3 Banjar. The research employed an experimental approach, where students received direct instruction on fundamental chemistry concepts using Avogadro and ChemDraw. The topics covered included chemical compound nomenclature, bond length, bond angles, and molecular geometry optimization. Following the training, students were tasked with analyzing the geometry and nomenclature of simple molecules visualized through the software, linking their observations to previously learned chemistry concepts. The results indicate that the training significantly improved students understanding of molecular geometry and chemical compound nomenclature. Computational-based learning also proved to be more interactive and effective in fostering students' interest and critical thinking skills in understanding chemistry concepts. Based on the questionnaire results, 95% of students reported a high level of satisfaction with the materials and teaching methods applied. Thus, computational chemistry training using Avogadro and ChemDraw serves as an effective instructional strategy for enhancing students' critical thinking skills and preparing them to face technology-based learning challenges. This study is expected to serve as a reference for developing innovative teaching methods in chemistry education.